Keefektivan Metarhizium anisopliae Sebagai Agen Pengendali Hayati Terhadap Larva Lalat Musca domestica L. - Muhammad Amiruddin; Umrah Umrah; Muhammad Alwi (Biology Department, Mathematics and natural science, Tadulako University, 2012)
Research on the